Effect of Wuzi Yanzong on Reproductive Hormones and TGF-β1/Smads Signal Pathway in Rats with Oligoasthenozoospermia. (16th April 2019) - Yang, Zhuo; Zhang, Xi; Chen, Zhimin; Hu, Changjiang
Abstract : Introduction . Wuzi Yanzong (WZYZ) formula, a famous traditional Chinese medicinal prescription, has been widely used to treat kidney essence insufficiency-induced oligoasthenozoospermia in ancient and modern clinical practice. Previous studies have demonstrated that WZYZ formula exhibits significantly therapeutic activity. The aim of this study was to evaluate the effect of WZYZ formula on the reproductive hormone levels and the TGF- β 1/Smads signal pathway in the testis, to explore the underlying mechanisms of WZYZ formula to improve spermatogenic function of testis in rats with oligoasthenozoospermia. Materials and Methods . In order to control the quality of the drug, the main components of the WZYZ formula were analyzed by HPLC. A rat model of oligoasthenozoospermia was established, by daily administration of tripterygium glucosides for 4 weeks, and treated with 1.62g/kg of WZYZ formula. The testes were histopathologically examined and serum levels of gonadotropin release hormone (GnRH), estradiol (E2), follicle-stimulating hormone (FSH), testosterone (T), and luteinizing hormone (LH) were measured by ELISA. TGf- β 1, Smad2, and Smad4 mRNA and protein levels in the testis were evaluated by immunohistochemistry (IHC), quantitative real-time RT-PCR (qRT-PCR), and Western blotting (WB). Result . Oral administration of WZYZ formula restored testicular structure and significantly increased the histology score in the oligoasthenozoospermic rats. In addition, WZYZ also significantly increased the serum levels of GnRH, LH, E2, and T and decreased that of FSH. Meanwhile, TGf- β 1, Smad2, and Sma4 expression levels were significantly decreased. Conclusions . WZYZ alleviates oligoasthenozoospermia by restoring the reproductive hormones and targeting the TGf- β 1/Smads pathway.